United Republic of Tanzania : Poverty Reduction Strategy Paper: Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2012)
This Joint Staff Advisory Note reviews Tanzania's Second National Strategy for Growth and Reduction of Poverty (NSGRP-MKUKUTA II) (2010/11-2014/15). MKUKUTA II provides an operational framework for achieving the Millennium Development Goals and Tanzania's Development Vision 2025, which aims to transform Tanzania into a middle-income country. Key recommendations are to expand fiscal space through improving spending efficiency and enhancing domestic revenue mobilization in line with its potential, decisive actions to improve the investment climate, and better specification of costing and realistic financing.